2013
DOI: 10.2172/1167437
|View full text |Cite
|
Sign up to set email alerts
|

2012 wind technologies market report

Abstract: Annual wind power capacity additions in the United States achieved record levels in 2012, motivated by the then-planned expiration of federal tax incentives at the end of 2012 and recent improvements in the cost and performance of wind power technology. At the same time, even with a short-term extension of federal tax incentives now in place, the U.S. wind power industry is facing uncertain times. It will take time to rebuild the project pipeline, ensuring a slow year for new capacity additions in 2013. Contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 0 publications
0
74
0
Order By: Relevance
“…New turbines’ nameplate capacity averaged 2.4 megawatts, and rotors averaged more than 115 meters. These larger turbines improved overall performance, with capacity factors climbing to 42% (Wiser & Bolinger, 2019).…”
Section: Factors Driving the Us Electricity Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…New turbines’ nameplate capacity averaged 2.4 megawatts, and rotors averaged more than 115 meters. These larger turbines improved overall performance, with capacity factors climbing to 42% (Wiser & Bolinger, 2019).…”
Section: Factors Driving the Us Electricity Transitionmentioning
confidence: 99%
“…In 2008, for instance, no turbines in the United States used rotors 100 meters or longer. By 2018, 99% of all newly installed turbines held rotors at least that length, with many even longer (Wiser & Bolinger, 2019). As individual turbines grow larger, they increasingly benefit from greater efficiency and performance.…”
Section: Factors Driving the Us Electricity Transitionmentioning
confidence: 99%
“…Most early studies estimated these costs below $5/MWh of wind energy, although one study approached $9/MWh of wind energy (Wiser and Bolinger 2008). Subsequent studies that had similar objectives confirmed these findings: most predicted costs below $5/MWh of wind energy, and all studies predicted less than $12/MWh of wind energy (Wiser et al 2013).…”
Section: Lessons Learned From Wind Integration Studiesmentioning
confidence: 90%
“…When 20% Wind Energy by 2030 was published, experience integrating wind energy into power systems was limited-wind energy penetration was more than 7% in some states and 1.1% nationally (Wiser and Bolinger 2008). Since that time, however, wind energy penetration has increased substantially-to more than 20% in some states and 4.2% nationally (Wiser et al 2013). With respect to wind integration studies, although the basic methodology had been established by 2008, the techniques and tools employed to conduct these types of analyses were, and still are, very much in development.…”
Section: Lessons Learned From Wind Integration Studiesmentioning
confidence: 99%
See 1 more Smart Citation